Evaluation of plasma ACTH in the metyrapone test is insufficient for the diagnosis of secondary adrenal insufficiency - Papierska, Lucyna; Rabijewski, Michał; Migda, Bartosz; Leszczyńska, Dorota; Nowak, Karolina; Łebek-Szatańska, Agnieszka; Glinicki, Piotr; Zgliczyński, Wojciech (Frontiers in Endocrinology, 2022)
Objective: To determine whether a single measurement of ACTH instead of less available in daily practice 11-deoxycortisol assay is sufficient to rule out or confirm secondary adrenal insufficiency (SAI) in the short Metyrapone test. Design: A retrospective analysis of diagnostic tests (Metyrapone and Synacthen tests) performed at our Center between 2016 and 2018 in patients with suspicion of secondary adrenal insufficiency. Material and Methods: In 103 patients short metyrapone test was performed with assessment of 11-deoxycortisol and ACTH concentration after Metyrapone administered at midnight. In 89 of them short Synacthen (SST) test was also done (1 or/and 250 mcg 1-24ACTH). ROC curves have been performed to evaluate the diagnostic performance of ACTH level in metyrapone test as the predictor of secondary adrenal insufficiency (SAI) analysing sensitivity and specificity for various possible thresholds proposed in literature. Results: 40 (39%) of examined subjects were diagnosed as SAI, basing on post-Metyrapone 11-deoxycortisol concentration below 70 μg/l. In this group ACTH concentration was 128.1 ng/l (95% CI 96.8-159.4) versus 289.9 ng/l (95% CI 249.1-330.9) in patients with proper adrenal response. There was only a moderate positive correlation between ACTH and 11-deoxycortisol concentrations (r=0.5; p<0.05). The best cut off value of ACTH in relation to 11-deoxycortisol serum concentrations was 147 ng/l - with sensitivity of 73.2% and specificity 83.9%. However, plasma ACTH was>200ng/ml (the highest threshold proposed in literature) in 8 cases (20%) with positive diagnosis of SAI made on the basis of low 11-deoxycortisole and confirmed in short Synacthen test. Conclusion Our results indicate that for a valuable evaluation of the results of the metyrapone test, the more readily available plasma ACTH assay cannot replace the measurement of 11-deoxycortisol concentrations.